The contribution of FADAMA III programme to food availability in Cross River, and Akwa Ibom States, Nigeria - Etim Edet Okon Ubokuloh; Onyendinachi Iheanacho; Glory Edim Inok (Universitas Negeri Makassar, 2025)
This study investigated FADAMA III programme and food security in Akwa Ibom and Cross River States. The population of the study consists of the entire staff and household beneficiaries of FADAMA III programme in Akwa Ibom and Cross River States numbering 8,040. This study applied both stratified and quota sampling techniques. 400 respondents drawn from the staff and household beneficiaries of FADAMA III programme was used as the sample size. 67 respondents were selected from the six senatorial districts in Akwa Ibom and Cross River States. The instrument for data collection was a structured questionnaire. The data collected were analysed using chi-square statistical analysis to test the null hypothesis at 0.05 level of significance; and the result of the analysis revealed that: FADAMA III programme has a significant effect on food availability, food affordability, food accessibility and food acceptability in Cross River and Akwa Ibom States, Nigeria. Based on the findings of the study, it was recommended, among others, that the government of Akwa Ibom and Cross River States should expand the scope of the FADAMA III Agriculture Development Programme beyond cultivation, rearing and production of agricultural produce and also include agro-business to boost the income of farmers and beneficiaries.